Production techniques of PV's and polycrystalline PV performance analyses for permanent resistive load - (:unkn) unknown (My University, 2009)
Photovoltaic (PV) panels which are used to convert solar energy to electrical energy one of the fastest growing source on energy sector. Their efficiencies are increasing day by day with new technologies. Photovoltaic's average efficiencies are still 15-20% in daily usage. In this study general photovoltaic production techniques are explained briefly. New technological developments affect these production techniques so the new methods on photovoltaic production are examined. During one year period polycrystalline PV performance which feeds the permanent resistive load is tested experimentally for Istanbul-Goztepe.
Keywords: D.C. loads; Energy consumption; Photovoltaic; Production techniques